P613 Social Media Analytics for Inflammatory Bowel Disease – What Are We Missing?. (27th May 2021) - Kumar, L; Kiely, L; O'Riordan, A; Barry, P
Abstract: Background: Increasingly, Inflammatory Bowel Disease (IBD) patients are using social media to disseminate information, share experiences and address queries. Gastroenterologists can play an important role in IBD care by better understanding trends in patients' perception of their disease. This study aimed to identify trending topics and misconceptions of disease for early targeted education based off patients' interactions and activity on social media. Methods: Utilising an established social media analytics program, we extracted social media posts relating to IBD over a 30-day period between 11/05/2020 and 10/06/2020. The most common hashtags and frequently used words were retrieved from these posts, analysed and qualitatively coded. Additional analysis was performed to evaluate user mentions for specific key words identified from the ECCO consensus for Complementary and Alternative Medicine (CAM) and psychotherapy. Results: 22, 375 social media posts were reviewed. Twitter was the most common platform with 12, 977 posts (58%). Most posts originated from North America and Europe (81%). Amongst common hashtags and words, patients most frequently referenced community groups (n=8094) for example "#crohnswarrior", followed by terms related to treatment (n=3256), and lifestyle (n=2446). Symptom-related terms were less frequently referenced (n=2031). Of mentions relating to diet and nutrition, 'gluten free' was mentioned most frequently (466/2911, 16.0%), followed by 'vegan' (374/2911, 12.8%), and 'plant based' (342/2911, 11.7%). There was a temporal association with these posts which was demonstrated by hashtags (n=1397) and mentions (n=485) referencing 'World IBD Day' which occurred on the 19th of May as well as hashtags (n=391) and mentions (n=1475) referencing the COVID 19 pandemic. Analysis of CAM mentions highlighted patients' interest in "exercise" as a manipulative and body-based intervention (2015/2088, 96.5%), "cannabinoids" as a herbal and dietary intervention (816/2144, 38.1%) and "yoga" as a mind-body intervention (175/415, 42.2%). 3435 mentions were generated from our psychological key word search. These included terms such as fatigue (28.2%), anxiety (20.1%), depression (13.8%) and suicide (2.2%). Conclusion: Our study identified areas where patients' needs, concerns and queries may be unmet by current clinical practices. Further development of our analytical model can aid gastroenterologists in bridging this gap and providing more holistic patient care.